What Drives Individual Health Expenditure in Switzerland? - Marcel Bilger; Jean-Paul Chaze (Swiss Journal of Economics and Statistics, 2008)
The explanatory factors of individual healthcare consumption are studied by means of healthcare expenditures from the 2000–2005 Swiss Household Income and Expenditure Survey (SHIES). In order to tackle the issues of large number of null expenditures and skewed distribution of positive outcomes, the family of Box-Cox censoring models (Chaze, 2005) is applied. The results show that the use of SHIES data makes it possible to reveal many important factors of individual healthcare consumption, and that the role played by healthcare supply density variables is consistent with the theory of induced demand.
Keywords: C24; D12; I11; 330; healthcare demand; health expenditure; hurdle models; Box-Cox